Large-scale evaluation of 2, 4-D choline off-target movement and injury in 2, 4-D-susceptible soybean. (26th February 2022) - Werle, Rodrigo; Mobli, Ahmadreza; Striegel, Sarah; Arneson, Nicholas; DeWerff, Ryan; Brown, Ashli; Oliveira, Maxwel
Abstract: Enlist E3 TM soybean cultivars permit over-the-top application of labeled glyphosate, glufosinate, and 2, 4-D choline products. Increased Enlist E3 TM trait adoption and use of 2, 4-D choline postemergence across U.S. soybean production systems raise concerns regarding potential for 2, 4-D off-target movement (OTM). A large-scale drift experiment was established near Sun Prairie, WI, and Arlington, WI, in 2019 and 2020, respectively. A 2, 4-D-resistant soybean cultivar was planted in the center of the field (∼3 ha), while the surrounding area was planted with a 2, 4-D-susceptible cultivar. An application of 785 ae ha −1 2, 4-D choline plus 834 g ae ha −1 glyphosate was completed within the center block at R2 and V6 growth stages on August 1, 2019, and July 3, 2020, respectively. Filter papers were placed in-swath and outside of the treated area in one upwind transect and three downwind transects to estimate particle deposition. Low-volume air samplers ran for the 0.5-h to 48-h period following application to estimate 2, 4-D air concentration. Injury to 2, 4-D-susceptible soybean was assessed 21 d after treatment (0% to 100% injury). The 2, 4-D deposition in-swath was 9, 966 and 5, 727 ng cm −2 in 2019 and 2020, respectively. Three-parameter log-logistic models estimated the distance to 90% reduction in 2, 4-D deposition (D90 ) to be 0.63 m and 0.90 m in 2019 and 2020, respectively. In 2020, the 2, 4-D air concentration detected was lower for the upwind (0.395 ng m −3 ) than the downwind direction (1.34 ng m −3 ), although both were lower than the amount detected in-swath (4.01 ng m −3 ). No soybean injury was observed in the downwind or upwind directions. Our results suggest that 2, 4-D choline applications following label recommendations pose little risk to 2, 4-D-susceptible soybean cultivars; however, further work is needed to understand 2, 4-D choline OTM under different environmental conditions and the presence of other susceptible crops.